PENGARUH SOFT SKILLS DAN KETERAMPILAN INTERPERSONAL TERHADAP KEPEMIMPINAN KEPALA SEKOLAH - Ayu Lestari; Hilal Mahmud; Nilam Permatasari Munir (Kelola: Journal of Islamic Education Management, 2022)
This study aims: to determine the effect of soft skills and interpersonal skills on the leadership of school principals in SD/MI equivalent to Palopo City. This type of research uses quantitative research with an ex-post facto research design. The number of population is 80 school principals with a sampling using random sampling of 30 school principals. The research instrument used a questionnaire (questionnaire) and documentation. Furthermore, the statistical analysis technique used to process the results is descriptive statistical analysis using multiple linear regression equations using SPSS for Windows Version 20. The results of this descriptive study indicate that soft skills (X1) and interpersonal skills (X2) affect the principal's leadership (Y) at SD / MI equivalent to Palopo City where the Fcount value of 15,640 is greater than Ftable 3.34 and the significant value for soft skills and interpersonal skills is 0.000 <0.05 (H0 is rejected and H1 is accepted). So it can be interpreted that Soft Skills and interpersonal skills have a simultaneous and positive effect on the leadership of school principals in SD / MI Equal to Palopo City by 55%. While the remaining 45% is obtained by other variables not examined in this study.